1992
DOI: 10.1091/mbc.3.8.851
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and trafficking of prion proteins in cultured cells.

Abstract: Scrapie prions are composed largely, if not entirely, of the scrapie prion protein (PrPSc) that is encoded by a chromosomal gene. Scrapie-infected mouse neuroblastoma (ScN2a) and hamster brain (ScHaB) cells synthesize PrPSc from the normal PrP isoform (PrPC) or a precursor through a posttranslational process. In pulse-chase radiolabeling experiments, we found that presence of brefeldin A (BFA) during both the pulse and the chase periods prevented the synthesis of PrPSc. Removal of BFA after the chase permitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
214
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(237 citation statements)
references
References 68 publications
19
214
1
3
Order By: Relevance
“…7A). This observation is in accord with several results previously obtained both in vitro and in vivo with different detection techniques (41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Unglycosylated Prp Localization Is Mainly Intracellular Whesupporting
confidence: 93%
“…7A). This observation is in accord with several results previously obtained both in vitro and in vivo with different detection techniques (41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Unglycosylated Prp Localization Is Mainly Intracellular Whesupporting
confidence: 93%
“…This mAb is expected to react with full-length PrP Sc but not with the N-terminally truncated form of PrP Sc that is generated by endogenous enzymes after PrP Sc formation in the cells Taraboulos et al, 1992). The mAb 8D5 specifically immunoprecipitated PrP Sc from brain homogenates of prion-infected animals, similar to other PrP Sc -specific antibodies reported to date (Curin Serbec et al, 2004;Horiuchi et al, 2009;Korth et al, 1997;Paramithiotis et al, 2003;Ushiki-Kaku et al, 2010).…”
Section: Introductionsupporting
confidence: 52%
“…Recently, Godsave and colleagues reported that in RML strain-infected mouse brains, the majority of PrP Sc clusters were detected at the plasma membranes, including membrane invaginations and the site of cell-to-cell contact, whereas in the other subcellular regions such as synapses and intracellular vesicles, PrP Sc clusters were detected only occasionally by immuno-electron microscopic examination using an antibody that recognizes the N-terminal region of PrP (Godsave et al, 2013). The authors believed that PrP Sc detected by the anti-PrP N-terminus mAb Saf32 included nascent full-length PrP Sc , as the N-terminal region tends to be processed after generation of PrP Sc Taraboulos et al, 1992). Considered collectively, ultrastructural studies suggest the plasma membranes as the primary site for PrP Sc formation.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier binding studies, significantly higher binding of PrP C to raft-like lipids was shown as compared to other lipids, but it was pointed out that binding of PrP C was not exclusive to rafts (25). The formation of PrP C clusters was described in cell-culture studies (32)(33)(34)(35). For example, highdensity PrP C clusters on the surface of primary culture neurons were observed (32).…”
Section: Discussionmentioning
confidence: 94%